The Effect Of Transformational Leadership On Employee Performance In The Technical Implementation Unit Of The Public Works And Spatial Planning Office Of Binjai City - Swandi Pinem; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of transformational leadership on employee performance at the Technical Implementation Unit of the Public Works and Spatial Planning Office in Binjai City. The population in this study consisted of 109 employees. The hypothesis test results indicate that transformational leadership has a positive and significant impact on employee performance, with a t-value of 44.054, which is greater than the t-table value of 1.98238, and a significance value of 0.000, which is less than 0.05. The regression coefficient shows that an increase of 1 unit in transformational leadership results in a 0.957 unit improvement in employee performance, assuming other variables remain constant. Furthermore, the determination test results indicate an Adjusted R Square value of 0.960 or 96%, indicating a very high impact of transformational leadership on employee performance, while the remaining 4% is influenced by other factors not examined in this study.